2009
DOI: 10.1136/vr.164.17.519
|View full text |Cite
|
Sign up to set email alerts
|

Application of a protocol for the diagnosis of postweaning multisystemic wasting syndrome in Italy

Abstract: Samples of superficial inguinal and bronchial lymph nodes, ileum, tonsil and lung were taken from three to five pigs on each of 61 farms with a clinical history of postweaning multisystemic wasting syndrome (PMWS). The samples were examined histologically and by immunohistochemistry for porcine circovirus type 2 (PCV-2). PMWS was diagnosed in two stages: first, an evaluation of the haematoxylin and eosin-stained sections that identified the cases in which the characteristic PCV-2 cytoplasmic inclusion bodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Focal necrotizing bronchiolitis was present in four lungs, while 14 lungs had complicating bronchopneumonia. Twenty-two out of the 28 cases (78.6%) with PNP were pigs from farms confirmed as affected by PMWS (Sarli et al, 2009), whereas six were derived from farms unaffected by PMWS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Focal necrotizing bronchiolitis was present in four lungs, while 14 lungs had complicating bronchopneumonia. Twenty-two out of the 28 cases (78.6%) with PNP were pigs from farms confirmed as affected by PMWS (Sarli et al, 2009), whereas six were derived from farms unaffected by PMWS.…”
Section: Discussionmentioning
confidence: 99%
“…The study involved immunohistochemical assessment of samples of lung from 28 pigs with PNP. These affected animals were part of an investigation of porcine post-weaning multisystemic wasting syndrome (PMWS) on farms in northern and central Italy (Sarli et al, 2009). Only one of these pigs was SIV seropositive (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCV2 host range is limited to the genus Sus (Segalés et al 2005) comprising both wild boar and domestic pigs. Serological surveys (Rose et al 2002), immunohistochemistry (IHC) (Ghebremariam and Gruys 2005;Sarli et al 2009) and in situ hybridization (ISH) (Ghebremariam and Gruys 2005) show that PCV2 is ubiquitous and may be encountered in herds both with and without PMWS. Wild boar (Sus scrofa ssp scrofa) can also be infected by PCV2 (Hungary, Cságola et al 2006;Belgium, Sanchez et al 2001;Slovenia, Toplak et al 2004;Spain, Vicente et al 2004;Germany, Knell et al 2005) and suffer from PMWS (Canada, Ellis et al 2003;Germany, Schulze et al 2004;Brasil, Correa et al 2006;Croatia, Lipej et al 2007; Greece, Sofia et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Pathological assessment of body condition shows that many of the pigs selected for necropsy were in terminal health condition and samples for microscopic examinations by IHC might be false negative. Recent studies have shown that the diagnosis of PMWS and other affections connected with PCV2 infections in pigs is more reliable when applied to larger groups of pigs (Sarli et al 2008).…”
Section: Discussionmentioning
confidence: 99%